Dynamics Simulation Analysis of Tooth Root Crack Fault of Planetary Gearbox based on Torsional Vibration Signal - Wei Wei; Yunpeng Li; Yanshuai Yang (Jixie chuandong)
The vibration-based methods have been widely used in the tooth root crack fault diagnosis of planetary gearbox. Compared with traditional transverse vibration signal，torsional vibration signal is not affected by the modulation of time-varying transmission path in theory，so its frequency component is simple and it is easy to extract fault features. The torsional vibration signal extracted from dynamic model is analyzed to realize the fault diagnosis of tooth root crack fault. Firstly，the rigid-flexible coupling model of healthy planetary gearbox is established and verified. Then，based on healthy planetary gearbox model，three typical crack fault models are established，and the dynamic response signals are extracted. Finally，tooth root crack fault is diagnosed by analyzing transverse vibration signal and torsional vibration signal. The results show that torsional vibration signal is feasible to diagnose planetary gearbox crack fault，and has more advantages than traditional transverse vibration signal.